Comparing Methods for Quantifying and Analyzing Drosophila Aggression - Trannoy, Severine; Fernandez, Maria P; Certel, Sarah J (Cold Spring Harbor protocols, 2023)
Here, we highlight three different assays that are used to study aggression. The advantages and disadvantages of each assay are discussed, as examining different aspects of aggressive behavior presents distinct challenges to researchers. This is because aggression is not a singular behavioral unit. Rather, aggression is the result of interactions between individuals; and, as such, the initiation and frequency of these interactions are impacted by the assay parameters including the method of loading the flies into the observation chamber, the size of the chamber, and the animals' previous social experience. Thus, determining which assay to use depends on the overall question that is the subject of investigation.